Video authentication in HEVC compressed domain / Tew Yiqi - Tew, Yiqi (2016)
High Efficiency Video Coding (HEVC) is the latest video compression standard finalized in year 2013. While H.264/Advance Video Coding (AVC) is still the mostly deployed video-coding standard, HEVC is gaining ground, especially for storage and transmission of high-resolution videos such as High Definition (HD), 4K, 8K and beyond. In this thesis, video authentication based on information hiding technique is studied. The concept of authentication, layout and implementation are presented under the latest HEVC video compression standard. One of the unique properties of HEVC standard, i.e., combination of coding unit size, which is sensitive to video manipulation, is utilized in the proposed information hiding technique. A video authentication scheme is then put forward by exploiting this unique property of HEVC to embed authentication code based on a predefined mapping rule. In addition, temporal dependency is enforced, where the authentication tag generated in one video slice is embedded into its subsequent slice. Furthermore, multiple layers of authentication are presented to detect and localize the tampered regions in a HEVC video, as well as verifying the source / sender of the video using a shared secret key. Moreover, several encryption techniques are presented to incorporate with the proposed scheme to achieve video authentication in encrypted domain without compromising on compression efficiency. Video sequences from various classes (i.e., resolutions) are considered to verify the performance of the proposed multi-layer authentication scheme. Results show that, at the expense of slight degradation in perceptual quality, the proposed scheme is robust against video tampering within and across video slices. Lastly, a functional comparison is performed between the proposed authentication scheme and the conventional schemes for both plaintext and ciphertext (encrypted) videos.